2018
DOI: 10.1016/j.ijid.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus 16/18: Fabricator of trouble in oral squamous cell carcinoma

Abstract: The exposure to high risk strains of Human papilloma virus (16/18) in combination can be fabricotor of trouble (p<0.001, Adjusted odds ratio; 21.42) in OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The best ways to prevent OSCC are abstinence from smoking, alcohol, and chewable tobacco products. Another risk factor that is attributable to OSCC is HPV infection [3]. In Pakistan, OSCC is the most common malignancy reported in males with twice the incidence as compared to females [1].…”
Section: Introductionmentioning
confidence: 99%
“…The best ways to prevent OSCC are abstinence from smoking, alcohol, and chewable tobacco products. Another risk factor that is attributable to OSCC is HPV infection [3]. In Pakistan, OSCC is the most common malignancy reported in males with twice the incidence as compared to females [1].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, previous study reported significant association between HPV-16 and chewed tobacco users. 21 The plausible reasons for the difference in findings could be related to sample size (100 oral squamous cell carcinomas compared to 50 HNSCC cases in the current study). Furthermore, we couldn't find statistically significant association between HPV-16 and age and gender which is in accordance with previous studies, however, others reported significant association of male predominance in HPV-associated HNSCC.…”
Section: Discussionmentioning
confidence: 74%
“…The HPV genotypes detected in head and neck squamous cell carcinoma (HNSCC) might differ from those in cervical cancers. HPV16 remains the most prevalent detected type (1.6–60.7%), followed by HPV31 (1.6–79.2%), HPV18 (0.7–15.1%), HPV56 (0.5–15.1%), HPV52 (2%), HPV33 (1.2%), and HPV35 (0.5%) [ 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Intriguingly, HPV31 (79.2%), HPV45 (87.4%), and HPV68 (49.1%) have been reported to have particularly high rates in Singapore.…”
Section: Hpv Genotype Distribution In East Southeast and South Asiamentioning
confidence: 99%
“…For HNSCC samples with a single HPV infection, most of the samples have been found to be positive for HPV16. Other detected hrHPV types include HPV31, 18, 56, 52, 33, and 35 [ 84 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Additionally, samples detected with HPV16/18 co-infection and multiple HPV genotypes were also reported [ 110 ].…”
Section: Hpv Genotype Distribution In East Southeast and South Asiamentioning
confidence: 99%